Sonication Enhancement of Capsaicin Formation in Callus of Chili Pepper, Capsicum annuum L. - Masyab, Hikmat M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The current study investigates the induction of callus from leaf explants of chili pepper Capsicum annuum L. coupled with the isolation of capsaicin from alcoholic extracts. To determine which isolated alkaloid has a positive reaction, the DragenDroff test is used. Alkaloid is identified using conventional diagnostic techniques, such as measuring the absorbance values of the isolated alkaloid with an ultraviolet spectrophotometer, the alkaloid is identified. The results show a complete identity among them, and with control. Thin layer chromatography data showed a 0.8 cm distance between one location from each tested sample with the same rate, which is 0.8 cm from the control’s rate flow value. The chemical structure of studied samples is subsequently determined using nuclear magnetic resonance, which reveals similarities between the isolated alkaloid’s structure and standard capsaicin. A quantitative analysis of the isolated alkaloids revealed variations in the amounts for generated explants relative to other explants. This study shows that fruits are the most effective source of alkaloids. It’s interesting to note that the composition of the explant and the sonicated callus are identical. Since capsaicin discovery, it is used as a homeopathic remedy to treat burning pain using the concept of “treating like with like” or counterirritant, relieve minor pain associated with rheumatoid arthritis or muscle sprains and strains and due to large consumption of this fruit recently, the current study done to find out the structure and quantity.